A study of identity construction in political discourse - Qaiwer, Shatha Naiyf (2016)
This thesis interrogates the construction of identity and self-presentation strategies in the discourse of the current President of the United States of America, Barack Hussein Obama. The study seeks to answer questions about how the President constructs the various identities evident in his discourse, what kinds of resources are drawn upon, and how the resulting identities contribute to gain the support of the audience and the progression of political discourse in general.